The effect of the extract of pasak bumi roots (Eurycoma longifoliaJack.) on liver function - Panjaitan, Ruqiah Ganda Putri; Manalu, Wasmen; Handharyani, Ekowati; ., Chairul (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
The aim of this research is to study the effects of the methanol extract and its derived fraction (n-hexane, chloroform, ethyl acetate, and methanolwater) on liver function of male rats. The treatment groups were administered 500 mg/kg body weight of metanol extract and its derived fractions (n-hexane, chloroform, ethyl acetate, n-butanol, methanol-water) of E. longifolia for 7 consecutive days. Positive control group received 25 mg silymarin/kg body weight and negative control group received 2 mL aquadest/kg body weight daily for 7 consecutive days. Liver function was monitored by measuring alanine transaminase (ALT), aspartate transaminase (AST), total protein, alkaline phosphatase (ALP), total bilirubin, direct bilirubin, and indirect bilirubin consentrations in the serum. Compared with control, oral administration of methanol extract and derived fractions of methanol extract of E. longifolia root had no significant effects on liver function (p>0.05). Methanol-water fraction gave similar results to silymarin.Key words: Eurycoma longfolia Jack.,liver function, biochemical blood Histopathologi